A Conceptual Framework Toward Understanding of Knowledge Acquisition Sources and Student Well-Being - Xu, Yan; Peng, Michael Yao-Ping; Shi, Yangyan; Wong, Shwu-Huey; Chong, Wei-Loong; Lee, Ching-Chang (Frontiers in Psychology, 2020)
There are a multitude of factors influencing student employability, with all previous studies basing their conclusions upon predetermined variables according to different theories and exploring the relevance between them. In this study, teachers' knowledge transfer and market orientation—are put forward on the basis of the marketing concepts in order to explore the conspicuousness between various factors within the structural model. This study uses students from colleges in Taiwan and mainland China, and purposive sampling is adopted to acquire samples required for statistics. A total of 1222 valid questionnaires were collected from Taiwanese and Mainland China students. The results indicate that knowledge transfer, market orientation and absorptive capacity have significant impacts on student employability, that the absorptive capacity has a positive moderating effect on the influence of knowledge transfer and market orientation on student employability. Based on results and findings, this study will provide suggestions for theoretical and practical implications.